2020
DOI: 10.1113/jp279573
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral chemoreflex control of fetal heart rate decelerations overwhelms the baroreflex during brief umbilical cord occlusions in fetal sheep

Abstract: The majority of intrapartum decelerations are widely believed to be mediated by the baroreflex secondary to brief umbilical cord occlusions (UCOs) but this remains unproven. r We examined the responses to brief-UCOs in fetal sheep and compared these to a phenylephrine-stimulated baroreflex in a separate cohort. A further cohort was instrumented with near-infrared spectroscopy to measure cerebral oxygenation during UCO. r The first 3-4 s of the brief-UCOs were consistent with a baroreflex, and associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 56 publications
5
63
1
Order By: Relevance
“…The delayed rise in MAP during carotid occlusion is additionally consistent with the sympathetic efferent arm of the peripheral chemoreflex, which induces hypertension via peripheral vasoconstriction (36). It is notable that an immediate increase in MAP was not observed during carotid occlusion.…”
Section: Fetal Responses During Ischemiasupporting
confidence: 69%
“…The delayed rise in MAP during carotid occlusion is additionally consistent with the sympathetic efferent arm of the peripheral chemoreflex, which induces hypertension via peripheral vasoconstriction (36). It is notable that an immediate increase in MAP was not observed during carotid occlusion.…”
Section: Fetal Responses During Ischemiasupporting
confidence: 69%
“…First, the key efferent response of the Bezold-Jarisch reflex that would distinguish it from the peripheral chemoreflex is peripheral vasodilation due to sympathetic nervous activity withdrawal (5,6). We have shown using chemical sympathectomy with 6-hydroxy-dopamine that sympathetic nervous system-mediated peripheral vasoconstriction is maintained throughout a prolonged series of repeated UCOs despite the onset of arterial hypotension (6,7).…”
mentioning
confidence: 99%
“…The article by Lear et al . (2020) in this issue of The Journal of Phsyiology reports on experiments in fetal sheep (∼125 days gestation) designed to test the comparative roles of baroreceptor‐mediated bradycardia associated with umbilical cord occlusion in utero vs . bradycardia mediated by chemoreception.…”
mentioning
confidence: 99%
“…In this report, Lear et al . (2020) found that both short episodes of repeated complete cord occlusions and longer sessions of asphyxia showed an initial hypertensive phase with a clear fetal heart rate (FHR) suppression which lasted only a few seconds. The early response was very similar to the changes in heart rate (FHR) associated with an increase in mean arterial pressure (MAP) during phenylephrine infusion experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation